Antioxidant efficiency and mechanisms of green tea, rosemary or maté extracts in porcine Longissimus dorsi subjected to iron-induced oxidative stress. (15th November 2019) - Zhou, Feibai; Jongberg, Sisse; Zhao, Mouming; Sun, Weizheng; Skibsted, Leif H.
Highlights: Hydrophobic rosemary extract (RE) protected meat by inverted dose-dependent action. RE was effective in preventing lipid oxidation, but had no influence on myoglobin. Hydrophilic maté (ME) and green tea extract (GTE) protected myoglobin and lipids. Higher concentrations of ME and GTE reduced thiol oxidation and radical formation. Higher concentrations of ME and GTE increased initial oxygen consumption rates. Abstract: Plant extracts from rosemary (RE), green tea (GTE), and maté (ME) were compared for the protection against iron-induced oxidation in porcine homogenates at total phenolic concentrations from 25 to 250 ppm. Lipid oxidation as indicated by TBARS was in all cases sufficiently suppressed, especially for RE. Hydrophobic RE retarded overall oxidation in the homogenates with an inverted dose-dependent response. Optimum delay of oxygen consumption was found at the lowest concentration applied, similar to protection against thiols and formation of protein radicals as measured by ESR, whereas the high concentration increased oxygen consumption and caused additionally thiol loss possibly due to thiol-quinone interactions, generating protein-phenol complexes. Hydrophilic ME or GTE increased the initial oxygen consumption rate as an indication of prooxidant activities at elevated concentrations. However, they were found to protect myoglobin and protein at those high concentrations with GTE being more efficient, possibly due to better chelation effect.